Tinjauan Hukum Islam Terhadap Kekerasan Gender Berbasis Online - Syamsir, Syamsiar; Aisyah, Siti (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
Online gender-based violence is a term used for any form of action that makes a person feel insecure, attacks a person’s gender or sexuality and is facilitated by the internet and technology. This study aims to 1) what forms of online-based gender violence are and what causes the violence to occur. 2) with the results of the analysis of these questions, what solutions are offered by Islamic law in handling the problem of online-based gender violence. The method used is data collection techniques with library research methods. The data were collected from the article entitled Islamic law on gender based sexual violence and other journals about cases of online based gender violence. From the results of the study, it was found that this type of violence is usually caused by a violation of privacy and or taking actions based on consent (consensus) on one or many individuals at once. If someone commits violence, in this case it is online-based gender violence, it means that humanity is in trouble. Therefore, Islam teaches him to repent and "islah". Islam calls for repentance and forgiveness not only for the perpetrator, but especially for the victim.